HUBUNGAN ASUPAN NATRIUM DENGAN TEKANAN DARAH PADA PEGAWAI DI SMA NEGERI 1 BATANG - Sevena Nur Ratnadewi; Muflihah Isnawati; Setyo Prihatin (JURNAL RISET GIZI, 2015)
Background: Hypertension is a condition where there is an increase in pressure. One of the main causes of hypertension is a lifestyle and a wrong diet. Preserved foods and kitchen salt and high amounts of flavoring can increase blood pressure because they contain excessive amounts of sodium.Objective: To determine the relationship between sodium intake and blood pressure in employees at SMA N 1 Batang.Method: This study was a clinical nutrition field study with a cross sectional approach. The sample was 50 people in SMA N 1 Batang which were determined by random sampling. Data collected in the form of general data samples obtained through the form of collecting data samples, data on sodium intake through a semi-quantitative food frequency form, and blood pressure through measurements using a spignomanometer. Test statistics are used to analyze the relationship between variables using the Pearson Product Moment correlation test.Results: The results showed that 58.0% of the samples had enough sodium intake and 64.0% of the samples had normal blood pressure. The results of statistical tests show that there is a relationship between sodium intake and systolic and diastolic blood pressure with a value of p 0.05.Conclusion: There is a correlation between sodium intake and blood pressure in employees in SMA 1 Batang.